Hemorragia uterina relacionada a multiparidad. - Arreaga Flores, Ginger Pamela (2019)
It is worth mentioning that this research project points out the morbidity of postpartum hemorrhage, so it is done retrospectively, descriptively, realistically and documentaryly. The Alfredo Noboa Montenegro General Hospital in the city of Guaranda, Gyneco-obstetrics service, where there are approximately 180 eutocic deliveries per month, of which about 1 or 2 become complicated in a way moderate. It is established that although race, age, number of pregnancies, parity, level of education, are not factors that influence alarmingly so that this type of hemorrhagic events occur, it is described that the greater the number of deliveries, the lower the contractile capacity of the Uterine myometrium is there, the truth is that it happens and it is a reality in our environment, so that awareness and prevention of those factors that predispose it is proposed.